Relationship between dynamic balance and quality of life in participants of physical activity in a program for old people - Hauser, Eduardo (2015)
Introduction: Postural balance is one of the most important factors associated to falls. Physical activity has been a tool to improve this balance. Objective: To investigate the association between dynamic balance and quality of life in participants of an extension project focused on physical activity for older adults. Methods: A cross-sectional and ex post facto study was conducted. The sample consisted of 94 subjects. We used a sociodemographic questionnaire, test stand, walk 2.44 m and back to sit in a chair and the SF-36. Results: There were significant correlations between the dynamic balance and all domains of the SF-36, included general sum of quality of life. This result indicates that higher scores in quality of life, better is the results of balance. Conclusion: Thus, we have to focus on working on body balance in order to improve quality of life of the elderly and their awareness of autonomy and independence in daily tasks.